Are Serum Metal Ion Levels a Concern at Mid-term Followup of Revision Knee Arthroplasty With a Metal-on-metal Hinge Design?. Issue 9 (September 2019) - Klasan, Antonio; Meine, Esko; Fuchs-Winkelmann, Susanne; Efe, Turgay; Boettner, Friedrich; Heyse, Thomas Jan
Abstract: Background: Elevated serum levels of chromium and cobalt ions in metal-on-metal (MoM) bearing surfaces is a well-known phenomenon in THA. However, few studies have addressed this issue in complex primary and revision knee arthroplasty using a MoM hinged mechanism, and no study, to our knowledge, has investigated knees with MoM hinges in patients without megaprostheses (tumor prostheses). Questions/purposes: We analyzed a series of patients who received MoM hinged revision knee prostheses and asked: (1) What are the serum metal ion levels at short-term followup? (2) Is there any correlation between metal ion levels and the Knee Society Score (KSS) at this followup? Methods: Between 2013 and 2017, we performed 198 revision knee arthroplasties, of which 32 (17.7%) were performed with a latest-generation MoM hinge knee design. In addition, three complex primary TKAs utilizing the same design were included in this study. The device features a metal-on-polyethylene bearing with a MoM hinge. During that period, our general indications for using a hinge were single-stage and two-stage revision surgeries, revisions with large bone defects, and primary TKA with > 20° mechanical malalignment or collateral ligament insufficiency. Of the 35 patients who received this device, 23 patients (65% of the overall group who received this implant; 11 males, 12 females) were available for followup at a median of 28 months (range, 13-61 months), and the remaining 12 (35%) patients were lost to followup. Our rationale for reporting before the more typical 2-year minimum was the finding of elevated serum ion levels with unclear clinical significance. Median age at the time of surgery was 68 years (range, 52-84 years). None of the patients included in the study had other implants with MoM bearings. Serum ion levels of chromium (III) and cobalt were assessed using mass spectrometry. Ion levels > 5 ppb were considered elevated. Clinical outcome was assessed using the original KSS. Results: Median chromium serum level was 6.3 ppb (range, 0.6–31.9 ppb) and median cobalt serum level was 10.5 (range, 1.0–47.5 ppb). Of the 23 patients, 16 had elevated serum ion levels. There was a moderate correlation between KSS and both chromium (p = 0.029, r = 0.445) and cobalt (p = 0.012, r = 0.502) levels. Conclusions: Elevated metal ion levels and radiolucent lines are common after surgery with this MoM hinge design at short-term followup, and we believe this finding is of great concern. Although no patient has yet been revised, these patients will be closely monitored. We recommend that serum ion analysis become a routine part of followup after any hinge TKA in an attempt to better understand the potential consequences of this phenomenon. Level of Evidence: Level IV, therapeutic study.